2021
DOI: 10.1091/mbc.e21-01-0014
|View full text |Cite
|
Sign up to set email alerts
|

Hsf1 activation by proteotoxic stress requires concurrent protein synthesis

Abstract: Heat shock factor 1 (Hsf1) activation is responsible for increasing the abundance of protein folding chaperones and degradation machinery in response to proteotoxic conditions that give rise to misfolded or aggregated proteins. Here, we systematically explored the link between concurrent protein synthesis and proteotoxic stress in the budding yeast, S. cerevisiae. Consistent with prior work, inhibiting protein synthesis before inducing proteotoxic stress prevents Hsf1 activation, which we demonstrated across a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(29 citation statements)
references
References 61 publications
0
29
0
Order By: Relevance
“…On the other hand, a strong translation at high temperature can be unfavorable because aggregation and degradation of proteins become prominent ( 51 ). Since the nascent proteins are in unfolded state, their high concentration at the ribosomes associated with a strongly translated mRNA can lead to aggregation at high temperatures ( 52 , 53 ). In the light of these conflicting expectations, we measured mRNA and protein levels upon heat shock to assess translation efficiency.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, a strong translation at high temperature can be unfavorable because aggregation and degradation of proteins become prominent ( 51 ). Since the nascent proteins are in unfolded state, their high concentration at the ribosomes associated with a strongly translated mRNA can lead to aggregation at high temperatures ( 52 , 53 ). In the light of these conflicting expectations, we measured mRNA and protein levels upon heat shock to assess translation efficiency.…”
Section: Resultsmentioning
confidence: 99%
“…A reduction in translation upon heat shock has been observed in several studies ( 54 , 64 ). A counterintuitive benefit of diminished translation is demonstrated by the observations that translation inhibitors can improve the survival of cells exposed to high temperatures ( 52 ), presumably due to the alleviation of proteotoxicity ( 53 ). Accordingly, the activity of a protein or associated physiological response can gain in importance despite reduced translation, as evidenced by our observation that the resistance to glucanases is enhanced after a heat shock (Figure 6D ).…”
Section: Discussionmentioning
confidence: 99%
“…Regulation of the majority, if not all of yeast RP genes depends on Ifh1p, which binds actively expressing Category I and II RP genes and a few RiBi genes, as determined by Chromatin Immunoprecipitation (ChIP). While inhibition of mTORC1 has little effect on Fhl1p occupancy, Ifh1p dissociates rapidly upon exposure to stress [59] , [60] , [63] , [76] , [84] , [85] , [86] , [87] . Ifh1p has also been proposed to play a role on Category III RP genes, as it may be detected on these genes by the more sensitive Chromatin Endogenous Cleavage (ChEC) approach in which the protein of interest is fused to micrococcal nuclease [37] .…”
Section: Rp Gene Regulation In Yeastmentioning
confidence: 99%
“…Ifh1p shows a dynamic response to environmental stress or nutrition deprivation, regardless of strain background, as communicated by mTORC1 inhibition [59] , [60] , [63] , [76] , [84] , [85] , [86] , [87] . According to one mechanism for removing Ifh1p from RP genes, which was illustrated using the W303 strain background, Ifh1p dissociates from RP gene promoters and associates with the UTP-C 90S pre-ribosome complex localized in the nucleolus.…”
Section: Rp Gene Regulation In Yeastmentioning
confidence: 99%
“…In fact, the protein aggregates that do form following physiological heat shock have been shown to largely consist of reversible biomolecular condensates that play an adaptive role in the stress response rather than proteotoxic aggregates (Iserman et al, 2020; Riback et al, 2017; Wallace et al, 2015). Moreover, several studies have demonstrated that depletion of amino acids or treatment with cycloheximide substantially diminishes the output of the HSR following heat shock, suggesting that ongoing translation and/or newly synthesized proteins (NSPs) may drive HSR activation (Masser et al, 2019; Triandafillou et al, 2020; Tye and Churchman, 2021). Thus, while the identities of the HSR ligands have not been established, NSPs are currently thought to be a major category of HSR activators.…”
Section: Introductionmentioning
confidence: 99%